Components of action representations evoked when identifying manipulable objects - Bub, Daniel N.; Masson, Michael E. J.; Lin, Terry (Frontiers in Human Neuroscience, 2015)
We examined the influence of holding planned hand actions in working memory on the time taken to visually identify objects with handles. Features of the hand actions and position of the object's handle were congruent or incongruent on two dimensions: alignment (left vs. right) and orientation (horizontal vs. vertical). When an object was depicted in an upright view, subjects were slower to name it when its handle was congruent with the planned hand actions on one dimension but incongruent on the other, relative to when the object handle and actions were congruent on both or neither dimension. This pattern is consistent with many other experiments demonstrating that a cost occurs when there is partial feature overlap between a planned action and a perceived target. An opposite pattern of results was obtained when the depicted object appeared in a 90-degree rotated view (e.g., a beer mug on its side), suggesting that the functional goal associated with the object (e.g., drinking from an upright beer mug) was taken into account during object perception and that this knowledge superseded the influence of the action afforded by the depicted view of the object. These results have implications for the relationship between object perception and action representations, and for the mechanisms that support the identification of rotated objects.